Architecture and the politics of gender in early modern europe - Hills, Helen ([S.l.] : Ashgate Pub Ltd, 2003)
Written by leading scholars in the field, the essays in this book address the relationships between gender and the built environment, specifically architecture, in early modern Europe. Scholars have begun to investigate the relationship between women and architecture and the ways in which architecture plays a part in the construction of gendered identities. So far the debates have focused on the built environment of the nineteenth and twentieth centuries to the neglect of the early modern period. This book focuses on early modern Europe, a period decisive for our understanding of gender and sexuality. Much thoughtful scholarship has enhanced our understanding of gender division in early modern Europe, but often this is blunted because it considers gender in isolation from other vital factors, especially social class. Central to the concerns of this book, therefore, is a consideration of the intersections of gender with social rank. Gender, Architecture and Power in Early Modern Europe makes a major contribution to the developing analysis of how architecture contributes to the shaping of social relations, especially in relation to gender, in early modern Europe.
Keywords: Architecture; Architecture and society; Architecture and women; Europe